Political Space Competition between Online and Conventional Transportation in Jakarta, Indonesia - Yusa Djuyandi; Arief Hidayat; Jumroh . (Journal of Social and Development Sciences, 2019)
The Presence of online transportation brings a new problem in Indonesia transportation market competition, many conventional transportation drivers, such as taxis, buses, motorcycle taxis, city transportation (Angkot) that reject the presence of online-based transportation. For conventional transportation drivers, the existence of online transportation has reduced their income because people prefer to use online transportation rather than conventional transportation. As the power holder, the government certainly has the right and authority to regulate and create policy harmonization for public transportation. This study uses qualitative method where primary data is obtained from 8 months observations, from November 2017 to June 2018. Secondary data are obtained from transportation ministerial regulations, regional regulations issued by the DKI Jakarta Provincial Government, and various discourses that developed in the media mass. Various data obtained are then sorted or filtered and crosschecked against other data. Based on our findings, the government has not been arranged adequate political space, especially for conventional transportation and online transportation in Jakarta. The slow pace of the central government to revise regulations regarding online transportation has triggered serious conflicts in the community. Digital revolution in the dimensions of online transportation in the public interest is what should be an integral part of previous government policies, and that never happened.